2008
DOI: 10.1042/bst0360543
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of COX-2 gene regulation

Abstract: Overexpression of the enzyme COX-2 (cyclo-oxygenase-2) is associated with various pathophysiological conditions, including inflammatory diseases and different cancers. Increased synthesis of COX-2 in fetal membranes and the myometrium is also linked with the onset of term and preterm labour. COX-2 gene regulation is controlled at various levels including gene transcription and post-transcriptional events. The present article focuses on the complexity of COX-2 gene regulation and reviews current concepts that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 17 publications
2
83
0
1
Order By: Relevance
“…miR-101b and miR-26b are differentially expressed in LPS-treated macrophages from young and aged mice In many cases, the altered miRNA level could reflect COX-2 expression at the post-transcriptional level (Harper and Tyson-Capper 2008). Previously, we have profiled the expression of miRNAs in LPS-treated and untreated macrophages from young and aged mice using the microarray technology and showed that miR101b and miR-26b were differentially expressed in the two age groups (Jiang et al 2012) (Fig.…”
Section: Lps Enhances Expression Of Cox-2 and Pge2 In Aged Mouse Perimentioning
confidence: 98%
“…miR-101b and miR-26b are differentially expressed in LPS-treated macrophages from young and aged mice In many cases, the altered miRNA level could reflect COX-2 expression at the post-transcriptional level (Harper and Tyson-Capper 2008). Previously, we have profiled the expression of miRNAs in LPS-treated and untreated macrophages from young and aged mice using the microarray technology and showed that miR101b and miR-26b were differentially expressed in the two age groups (Jiang et al 2012) (Fig.…”
Section: Lps Enhances Expression Of Cox-2 and Pge2 In Aged Mouse Perimentioning
confidence: 98%
“…In addition, COX-1 is highly expressed in gastric epithelial cells where it plays an important role in cytoprotection through the generation of prostanoids, such as prostaglandin E2 (PGE2) [31,33] . In contrast, COX-2 gene, a primary response one with many regulatory sites [34] , is constitutively expressed in some tissues in physiological conditions, such as the endothelium, kidney and brain, and in pathological conditions, such as in cancer [35] . In cancer cells, the major prostanoid produced through COX-2 is PGE2, which plays important roles in modulating motility, proliferation and resistance to apoptosis [36,37] .…”
Section: Mechanism Of Action Of Aspirinmentioning
confidence: 99%
“…The expression of the prostaglandin synthetase-2 gene (PTGS-2 ⁄ COX-2) is regulated at both transcriptional and post-transcriptional levels (9), and several studies have reported the role of )765G>C and )1195A>G polymorphisms in the promoter region as risk factors for various cancers (10). We have previously reported the possible association of polymorphisms )765G>C and )1195A>G with subgroups of patients with NMSC after transplantation (11).…”
Section: Introductionmentioning
confidence: 99%
“…It has 22 repeats of adenylate and uridylate-rich (AU-rich ⁄ AREs) elements, whose binding trans-acting factors influence the stabilization and ⁄ or mRNA processing and nucleocytoplasmic transport (9). Furthermore, 3¢UTR has many putative binding sites for several microRNAs (http:// www.targetscan.org) that might affect the stability and translation of mRNAs (9,14). Sequence variation affecting trans-acting factors or microRNA binding sites may interfere with mRNA stability and translation by altering polyadenylation, protein::mRNA and miRNA::mRNA regulatory interactions, contributing towards differential PTGS-2 expression and a substantial degree of interindividual variability in susceptibility to cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation